Optimal profits under environmental regulation: The benefits from emission intensity averaging - Benjamin Hampf; Kenneth Løvold Rødseth (Technische Universität Darmstadt, Department of Law and Economics, 2014)
In this paper we analyze the economic effects of implementing EPA's newly proposed regulations for carbon dioxide (CO2) on existing U.S. coal-fired power plants using nonparametric methods on a sample of 144 electricity generating units. Moreover, we develop an approach for evaluating the economic gains from averaging emission intensities among the utilities' generating units, compared to implementing unit-specific performance standards. Our results show that the implementation of flexible standards leads to up to 2.7 billion dollars larger profits compared to the uniform standards. Moreover, we find that by adopting best practices, current profits can be maintained even if an intensity standard of 0.88 tons of CO2 per MWh is implemented. However, our results also indicate a trade-off between environmental and profit gains, since aggregate CO2 emissions are higher with emission intensity averaging than with uniform standards.
Keywords: D24; L50; Q54; 330; environmental regulation; profit maximization; emission intensity averaging; nonparametric effciency analysis